Analisa Penerapan Metode Penyusutan, Umur Manfaat, dan Revaluasi Aset Tetap terhadap Kinerja Keuangan Perusahaan - Srikalimah Srikalimah; Rosyidatul Malikah (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to analyze the application of depreciation methods, useful life, and revaluation of fixed assets to the company's financial performance. The data analysis technique used is descriptive quantitative. The research was conducted at PG Ngadiredjo which is one of the business units of PT. Perkebunan Nusantara X. There are certain assets that need to be revalued in value every few days. Revaluation will affect the value of assets on the balance sheet. The purpose of this study is to analyze the application of depreciation methods, useful life, and revaluation of fixed assets to the company's financial performance. The results showed that the straight-line fixed asset depreciation method resulted in the lowest depreciation expense and the highest profit than the declining balance depreciation method and the number of year numbers method, which was Rp. 612,982,138 in 2017, and amounted to Rp. 949,809,316 in 2018 and 2019. In contrast, the declining balance method results in the highest depreciation load among the three methods used. The useful life of the assets applied by the company affects the calculation of depreciation expense. The increase in the value of the revaluation assets leads to an increase in the value of the assets presented on the balance sheet and an increase in comprehensive income on the income statement in the year of the revaluation. The highest ratio of fixed asset turnover, return on sales margin, and ROA occurred in 2019. The company can continue to use the straight-line depreciation method in calculating the depreciation expense of the assets it owns.